Perancangan Media Kreatif Iklan Layanan Masyarakat tentang Sampah pada Sungai Deli Wilayah Medan - Langgeng Syahputra; Titin Setiawati (Jurnal Indonesia Sosial Teknologi, 2022)
The public service advertisement that the author wants to create and do is a movement to manage and utilize waste into something meaningful and valuable to reduce the increasing number of waste around the city of Medan. This is also a way to guide the community so that people are more obedient to environmental hygiene issues, especially waste problems. The design of public service advertisements containing the theme "Don't Dirt Me" is obtained from regions, regions and regions, so the main problem in designing this Public Service Advertisement is from rivers full of garbage, and so on. From the information and data that has been obtained, the process and stages of a cleaning program in the Medan area, especially the Medan Deli River in the design that will be created, require systematic preparation, strategies, structures and methods. The design is done through data analysis, observation and interviews. By analyzing the data, the writer found some visual shadows such as illustrations, and colors. This cleaning design program completes the data, designs and applies it to posters, and creates selected designs that are made into the media such as the main and supporting ones, the Public Service Advertising Media keeping the river clean is ready to be placed in a very strategic location so that readers can see the Public Service Advertisement media properly. The designer will create public service advertisements in the form of: banners and posters. The results of this design can be recommended as an alternative model of inviting information, as an effort to increase discipline, and clean motivation, so that the environment becomes more awake and healthier for the surrounding community.